1990
DOI: 10.1056/nejm199009063231002
|View full text |Cite
|
Sign up to set email alerts
|

Latent Varicella–Zoster Viral DNA in Human Trigeminal and Thoracic Ganglia

Abstract: These findings indicate that after primary infection with varicella-zoster virus (varicella), the virus becomes latent in many ganglia--more often in the trigeminal ganglia than in any thoracic ganglion--and that more than one region of the viral genome is present during latency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(106 citation statements)
references
References 17 publications
1
104
0
1
Order By: Relevance
“…The observation that IE proteins were expressed in neural cells in the NOD-SCID mouse-human neural cell model while gE synthesis was reduced serves to validate reports about VZV gene transcription and translation in neural cells within human sensory ganglia obtained at autopsy and in animal models (2,4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Conclusions from autopsy specimens have been questioned because VZV gene expression might be triggered during the time required to obtain tissues, and infection of nonhuman neural cells in animals may not reproduce the VZV pathogenesis in the human host accurately.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The observation that IE proteins were expressed in neural cells in the NOD-SCID mouse-human neural cell model while gE synthesis was reduced serves to validate reports about VZV gene transcription and translation in neural cells within human sensory ganglia obtained at autopsy and in animal models (2,4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Conclusions from autopsy specimens have been questioned because VZV gene expression might be triggered during the time required to obtain tissues, and infection of nonhuman neural cells in animals may not reproduce the VZV pathogenesis in the human host accurately.…”
Section: Discussionmentioning
confidence: 68%
“…Herpes simplex virus 1 produces latency-associated antisense mRNA transcripts (LATs) in neuronal cell nuclei, and viral proteins are not detected in human autopsy specimens or animal models of persistent infection (6). In contrast, VZV has no LAT sequence, and transcription or translation of VZV genes encoding the IE major transactivating protein, IE62, the IE63 coregulatory protein, and ORFs 4, 21, 29, 40, and 66 has been reported in ganglia (2,4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…New formulations of the vaccine with high titres and increased stability of the virus, like the vaccine used for these studies, raise the response rate in the vaccinees without an increase in the number of serious adverse events (10,11). Additional concerns were raised by the persistence and reactivation of wild type VZV in elderly or immunodepressed patients (16,17). It has been shown that the OKA strain persists in vaccinees and that it can be reactivated in immunocompromised or healthy hosts; however, zoster rates were significantly lower and milder than in nonvaccinees (2).…”
Section: Discussionmentioning
confidence: 99%
“…Primary infection, usually in childhood, causes varicella (chickenpox), after which virus become latent in cranial nerve ganglia, dorsal root ganglia and autonomic ganglia along the entire neuraxis (1). As cellmediated immunity to VZV declines with advancing age and immunosuppression, VZV reactivates to produce herpes zoster (shingles), frequently complicated by postherpetic neuralgia (radicular pain that persists long after the disappearance of rash).…”
Section: Introductionmentioning
confidence: 99%